2010
DOI: 10.1186/1475-2840-9-56
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic changes with the onset of diabetes and the impact of aerobic exercise training in the Zucker Diabetic Fatty (ZDF) rat

Abstract: BackgroundEarly markers of diabetic autonomic neuropathy (DAN) in an electrocardiogram (ECG) include elevated R wave amplitudes, widening of QTc intervals and decreased heart rate variability (HRV). The severity of DAN has a direct relationship with mortality risk. Aerobic exercise training is a common recommendation for the delay and possible reversal of cardiac dysfunction. Limited research exists on ECG measures for the evaluation of aerobic exercise training in Zucker Diabetic Fatty (ZDF) rat, a model of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…In addition, QRS prolongation, which may occur due to decreased CV, is found in both STZ treated rats [36] and ZDF rats [27], as well as in diabetic humans [37]. This indicates that decreased CV may be an independent risk factor for development of ventricular arrhythmias in both type 1 and 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, QRS prolongation, which may occur due to decreased CV, is found in both STZ treated rats [36] and ZDF rats [27], as well as in diabetic humans [37]. This indicates that decreased CV may be an independent risk factor for development of ventricular arrhythmias in both type 1 and 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Along with these systemic alterations, ZDFs also demonstrate cardiac changes such as altered myocyte contraction and Ca 2+ signaling at 9 to 13 weeks of age [23], mild diastolic dysfunction and increased collagen content at 45 weeks of age [24], as well as increased cardiac levels of triacylglycerol at 6 and 7 weeks of age [25,26]. Alterations in the ECG with the onset of diabetes in ZDF rats have also been demonstrated [27]. These alterations include widening of the QRS intervals, which may indicate decreased ventricular CV.…”
Section: Introductionmentioning
confidence: 99%
“…In a diff erent study, VanHoose et al [ 23 ] investigated the eff ect of exercise training in obese rats using a velocity of 15 m.min − 1 for 40 min, 5 days per week for 7 weeks. These authors described signs of fatigue among the obese animals, which may suggest that those animals were in an intensity domain above their anaerobic threshold.…”
mentioning
confidence: 99%
“…These fi ndings are of great interest since they may serve as a basis for studies involving obese animal models and physical exercise. A valuable example of the importance of MLSS in obese rats (Zucker fa/fa) is the recent study of VanHoose et al [ 19 ] , which reported that these rats showed signs of fatigue, when they were allowed to rest for a few minutes. In this study, a velocity of 15 m.min − 1 during 40 min was used.…”
mentioning
confidence: 99%